Postprandial triglyceride-rich lipoproteins in insulin resistance and Type 2 diabetes. (October 2008) - Matikainen, Niina; Taskinen, Marja-Riitta
Recent evidence from prospective epidemiological large-scale studies have provided convincing proof for the role of nonfasting triglycerides, carried in VLDL and chylomicrons, as an independent risk factor for cardiovascular disease and death. Overproduction of large VLDL1 by the liver on one hand, and accumulation of apoB-48-containing triglyceride-rich lipoproteins (TRLs) on the other hand are present before overt hyperglycemia, highlighting the role of insulin resistance as an early pathogenic defect. Multiple insulin action sites demonstrate insulin resistance in the liver, adipose tissue and muscle, as well as in the intestine. Together, these perturbations of insulin action contribute to the overproduction of atherogenic VLDL and chylomicron remnant particles. Consequently, the vascular wall endothelium is exposed to exaggerated cholesterol influx resulting in endothelial dysfunction, oxidative stress and prothrombotic state during subsequent meals over the 24-h period. This overview summarizes current understanding of diabetic postprandial ''dysmetabolism'' and reviews recent data on TRL secretion and intravascular processing and removal accumulated during this decade. Various therapeutic strategies and future opportunities are also discussed.